Удобный способ синтеза N,N-диалкоксикарбаматов и N,N- диалкоксимочевин - Штамбург, Василий Георгиевич; Штамбург, Виктор Васильевич; Герасименко, М. В.; Мазепа, А. В.; Шишкин, О. В.; Зубатюк, Р. И.; Кравченко, С. В. (НТУ "ХПИ", 2012)
Предложен новый способ синтеза труднодоступных и стерически затрудненных N,N-диалкоксикарбаматов и N,N-диалкоксимочевин алкоголизом N-хлор-N-алкоксикарбаматов и N-хлор-N-алкоксимочевин, соответственно, в присутствии трифторацетата серебра. Ил.: 16. Библиография 24.

The new synthesis method of hard-to-reach and sterically hindered N,N-dyalkoxycarbamates and N,N-dyalkoxyureas by alkogolysys N-chloro-N-alkoxycarbamates anf N-chloro-N-alkoxyureas respectively in the presence of argentums trifluoroacetate has been proposed. Im.: 16: Bibliogr.: 24
The new synthesis method of N,N-dyalkoxycarbamates and N,N-dyalkoxyureas
Keywords: органический синтез; N-хлор-N- алкоксикарбаматы; N-хлор-N-алкоксимочевины; алкоголиз; трифторацетат серебра; organic Synthesis; N-chloro-N-alkoxycarbamates; N-chloro- N-alkoxyureas; argentums trifluoroacetate